2004
DOI: 10.1182/blood-2004-01-0361
|View full text |Cite
|
Sign up to set email alerts
|

Activated polymorphonuclear neutrophils disseminate anti-inflammatory microparticles by ectocytosis

Abstract: On activation, human neutrophils release microparticles, called ectosomes, directly from the cell surface membrane. Microparticles from platelets, endothelial cells, and monocytes were reported to support coagulation or to modulate vascular homeostasis by activating monocytes as well as endothelial cells. We find that neutrophil ectosomes have no proinflammatory activity on human macrophages as assessed by the release of interleukin 8 (IL-8) and tumor necrosis factor ␣ (TNF␣). On the contrary, ectosomes increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
302
2
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(333 citation statements)
references
References 29 publications
17
302
2
6
Order By: Relevance
“…Incubation of a macrophage cell line with PMN-derived ectosomes attenuates its activation by LPS and zymosan A and reduces the levels of inflammatory cytokines (i.e., IL-8, TNF-β) produced. PS present in the outer surface of ectosomes is found to be responsible for the immunomodulatory property of ectosomes (Gasser and Schifferli, 2004), and a specific receptor protein tyrosine kinase (i.e., Mer receptor tyrosine kinase) is involved in the intracellular signaling process (Scott et al, 2001). PMN-derived ectosomes also have an inhibitory effect on immature DCs (Eken et al, 2008;Gasser and Schifferli, 2004).…”
Section: Biological Roles Of Ectosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Incubation of a macrophage cell line with PMN-derived ectosomes attenuates its activation by LPS and zymosan A and reduces the levels of inflammatory cytokines (i.e., IL-8, TNF-β) produced. PS present in the outer surface of ectosomes is found to be responsible for the immunomodulatory property of ectosomes (Gasser and Schifferli, 2004), and a specific receptor protein tyrosine kinase (i.e., Mer receptor tyrosine kinase) is involved in the intracellular signaling process (Scott et al, 2001). PMN-derived ectosomes also have an inhibitory effect on immature DCs (Eken et al, 2008;Gasser and Schifferli, 2004).…”
Section: Biological Roles Of Ectosomesmentioning
confidence: 99%
“…PS present in the outer surface of ectosomes is found to be responsible for the immunomodulatory property of ectosomes (Gasser and Schifferli, 2004), and a specific receptor protein tyrosine kinase (i.e., Mer receptor tyrosine kinase) is involved in the intracellular signaling process (Scott et al, 2001). PMN-derived ectosomes also have an inhibitory effect on immature DCs (Eken et al, 2008;Gasser and Schifferli, 2004). Thus, when immature DCs are cultured with LPS in the presence of PMN-derived ectosomes, expression levels of the cytokines and costimulatory and adhesion ligands required for T cell activation are significantly reduced, compromising T cell activation.…”
Section: Biological Roles Of Ectosomesmentioning
confidence: 99%
“…Most of the data on PMN-derived EVs (called in these studies ectosomes) come from the laboratory of Dr. Schifferli [26,[34][35][36]39,40,45,[93][94][95][96]. They characterized the size and surface properties of EVs released upon fMLP-stimulation and came to the conclusion that both the in vitro and the in vivo generated EVs are right-side out [39,45].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 99%
“…They characterized the size and surface properties of EVs released upon fMLP-stimulation and came to the conclusion that both the in vitro and the in vivo generated EVs are right-side out [39,45]. Further, they demonstrated that PMN-derived EVs increased the secretion of the anti-inflammatory cytokine TGF-β1 from monocytes, whereas the stimulated release of IL-8, IL-10 and TNFα was decreased [40]. Secretion of TGF-β1 was induced also in monocyte-derived dendritic cells, where incubation with PMN-EVs interfered with the LPS-induced differentiation process indicated by a decrease of release of inflammatory cytokines, decrease of phagocytosis and T-cell stimulation [34].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 99%
“…Small membrane vesicles released into the circulation from activated platelets are described in the literature as microparticles (MP); these have major roles in blood coagulation by providing a large surface area for the assembly of clotting factors that bind to the exposed phosphatidylserine of the released MPs [30,31]. Activated human neutrophils release "ectosomes" that exhibit anti-inflammatory activity and mediate inhibition of DC maturation from cultured blood monocytes [26,27,32]. Particles secreted from the basolateral membranes of various epithelial cells during tissue development are called "argosomes" due to their involvement in the transfer of developmental morphogens between cells and the maintenance of morphogen gradients [33].…”
Section: P2x7r Regulation Of Plasma Membrane Microvesicle Releasementioning
confidence: 99%